Further studies on the morphology of three species of Rhopalopsole (Plecoptera, Leuctridae) - Xiao Yang; Yu-Zhou Du (Biodiversity Data Journal)
Rhopalopsole Klapálek, 1912, is a species-rich genus in the family Leuctridae, with more than 80 valid species known from the Oriental and eastern Palaearctic Regions.We recently examined specimens of Rhopalopsole Klapálek, 1912 from Hubei and Guizhou, China and provided a supplementary description of Rhopalopsole ampulla Du & Qian, 2011, Rhopalopsole exiguspina Du & Qian, 2011 and Rhopalopsole memorabilis Qian & Du, 2014. Additionally, we provide new images of these species to facilitate identification.